BAKTI SOSIAL DAN SOSIALISASI PENDIDIKAN DI GEREJA TORAJA JEMAAT LONDOKADAWANG, DESA PANA, KABUPATEN ENREKANG - Palalangan, Carolus Askikarno; Daud, Maiercherinra; Melani, Meissy; Tesa, Tesa; Christable, Arabelia Astrid; Palallo, Klaradelita; Rano, Erma Lola’ (Batara Wisnu : Indonesian Journal of Community Services, 2021)
Social Service is a community service activity to build and help the community. For example, the Toraja Church of the Getsemani Congregation of Po’poran, which is located in Pana’ village, Alla’ sub-district, Enrekang district, South Sulawesi, on June 5, 2021, This activity is a social activity for the construction and Service of a church that functions as a place of worship, as a place of education and means of community interaction. However, often these activities do not function optimally because the facilities and infrastructure are inadequate. Therefore, this activity serves to build and provide services to the Toraja Jetsemani Po’poran Church. The steps taken include renovating the church building, cleaning the environment, maintaining outdated facilities, and providing educational services to children in the church